Pemanfaatan Teknologi Artificial Intelligence Dalam Memasarkan Produk Secara Digital dan Dampaknya Terhadap Customer Repurchase Intention pada Shopee - Lang, Ratnawati; Saragih, Fry Melda; Hanoky, Alif (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Research exploring the impact of artificial intelligence (AI) technology in marketing products via e-commerce on consumer repurchase decisions remains limited. Therefore, this study aims to investigate the influence of AI-based product recommendations and chatbot quality on Shopee on consumer repurchase intention, mediated by consumer consideration. This study adopts an explanatory research approach. Data will be collected using a questionnaire created with Google Forms and distributed through social media to consumers who have made purchases on Shopee. Purposive sampling was employed, yielding 155 respondents. Analysis will be conducted using SmartPls3.0 and the partial least squares structural equation model (PLS-SEM). Findings indicate that chatbot quality in AI significantly impacts consumer consideration and repurchase intention, whereas product recommendations in AI do not. Additionally, consumer consideration mediates the relationship between chatbot quality and repurchase intention.